Job satisfaction with the interpersonal relationships of non-university education teachers, their relationship with situations of bullying or mistreatment and exploration of personal and contextual predictors - González Álvarez, María (Pulso. Revista de educación, 2020)
The main goal of this paper is to carry out an exploratory study on teachers’ job satisfaction in their interpersonal relationships and possible situations of harassment, mistreatment or aggression, according to sociodemographic variables and responsibility positions at school. To this purpose, an online consultation was launched among the teachers from the different regions of Spain using an ad hoc protocol that was filled in by 2,738 teachers. Cronbach reliability coefficient is .769. Descriptive analysis, media difference, and multivariate analysis were performed. Among the conclusions, teachers feel medium-high satisfaction at school in regards to management positions, teachers and students, they feel moderate satisfaction about families and medium-low satisfaction regarding the educational administration and inspection. There are a high percentage of teachers who state they have experienced possible situations of harassment, mistreatment or aggression. It seems appropriate to continue analyzing the interpersonal relationships related to teachers’ job satisfaction and it is urgently necessary to investigate situations of harassment, mistreatment or aggression experienced by them.
Keywords: Job satisfaction; education administration; mistreatment; management positions; relationships